2019
DOI: 10.1186/s12937-019-0454-2
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of a food frequency questionnaire for assessing dietary intake among Shanghai residents

Abstract: Background Few localized food frequency questionnaires (FFQ) have been developed and used in Chinese nutrition surveys despite China’s large population and diverse dietary habits. Method We analyzed data collected in two waves (six months apart) of the Shanghai Diet and Health Study in 2012–2013, from 1623 Shanghai residents (798 men and 825 women) older than 18 years. The results of 3-day 24-h dietary recalls (HDR) plus condiment weighing were used to evaluate the vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
29
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 22 publications
12
29
4
Order By: Relevance
“…Similarly, variability was associated with an overestimation or an underestimation of systematic errors. In this study, due to the correction for changes in the daily intakes, the deattenuated correlation coe cients increased, which was similar to the FFQ reliability studies from other special populations in China [23,43]. In addition to the correlation coe cients, we used quartile cross-classi cation agreements and the Bland-Altman plots to evaluate the validity of the two methods.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Similarly, variability was associated with an overestimation or an underestimation of systematic errors. In this study, due to the correction for changes in the daily intakes, the deattenuated correlation coe cients increased, which was similar to the FFQ reliability studies from other special populations in China [23,43]. In addition to the correlation coe cients, we used quartile cross-classi cation agreements and the Bland-Altman plots to evaluate the validity of the two methods.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, it has been widely used in large-scale nutritional epidemiology studies in different populations [22]. Because dietary habits greatly vary in populations with different regional, ethnic, dietary, or cultural backgrounds, the FFQ should be tailored, reproducible, and valid for use in a speci c population [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The lower correlation coefficients for iron and vitamin intakes observed in our study is not uncommon in FFQ validation studies (8,10,11,13,18). A meta-analysis of FFQ validation studies showed that pooled correlation coefficients of nutrient intakes ( total fat, protein, carbohydrate, alcohol, calcium, iron and vitamins) were lower for FFQ validated against 24-HRs rather than food record (17).…”
Section: Discussioncontrasting
confidence: 45%
“…The lower correlation coe cients for iron and vitamin intakes observed in our study is not uncommon in FFQ validation studies (8,10,11,13,18). A meta-analysis of FFQ validation studies showed that pooled correlation coe cients of nutrient intakes ( total fat, protein, carbohydrate, alcohol, calcium, iron and vitamins) were lower for FFQ validated against 24-HRs rather than food record (17).…”
Section: Discussioncontrasting
confidence: 39%